Impaired excitation–contraction coupling in muscle fibres from the dynamin2R465W mouse model of centronuclear myopathy. (21st November 2017) - Kutchukian, Candice; Szentesi, Peter; Allard, Bruno; Trochet, Delphine; Beuvin, Maud; Berthier, Christine; Tourneur, Yves; Guicheney, Pascale; Csernoch, Laszlo; Bitoun, Marc; Jacquemond, Vincent
Abstract : Key points: Dynamin 2 is a ubiquitously expressed protein involved in membrane trafficking processes. Mutations in the gene encoding dynamin 2 are responsible for a congenital myopathy associated with centrally located nuclei in the muscle fibres. Using muscle fibres from a mouse model of the most common mutation responsible for this disease in humans, we tested whether altered Ca 2+ signalling and excitation–contraction coupling contribute to muscle weakness. The plasma membrane network that carries the electrical excitation is moderately perturbed in the diseased muscle fibres. The excitation‐activated Ca 2+ input fluxes across both the plasma membrane and the membrane of the sarcoplasmic reticulum are defective in the diseased fibres, which probably contributes to muscle weakness in patients. Abstract: Mutations in the gene encoding dynamin 2 (DNM2) are responsible for autosomal dominant centronuclear myopathy (AD‐CNM). We studied the functional properties of Ca 2+ signalling and excitation–contraction (EC) coupling in muscle fibres isolated from a knock‐in (KI) mouse model of the disease, using confocal imaging and the voltage clamp technique. The transverse‐tubule network organization appeared to be unaltered in the diseased fibres, although its density was reduced by ∼10% compared to that in control fibres. The density of Ca 2+ current through CaV1.1 channels and the rate of voltage‐activated sarcoplasmic reticulum Ca 2+ release were reduced by ∼60% and 30%, respectively, in KI vs . control fibres. In addition, Ca 2+ release in the KI fibres reached its peak value 10–50 ms later than in control ones. Activation of Ca 2+ transients along the longitudinal axis of the fibres was more heterogeneous in the KI than in the control fibres, with the difference being exacerbated at intermediate membrane voltages. KI fibres exhibited spontaneous Ca 2+ release events that were almost absent from control fibres. Overall, the results of the present study demonstrate that Ca 2+ signalling and EC coupling exhibit a number of dysfunctions likely contributing to muscle weakness in DNM2 ‐related AD‐CNM. Key points: Dynamin 2 is a ubiquitously expressed protein involved in membrane trafficking processes. Mutations in the gene encoding dynamin 2 are responsible for a congenital myopathy associated with centrally located nuclei in the muscle fibres. Using muscle fibres from a mouse model of the most common mutation responsible for this disease in humans, we tested whether altered Ca 2+ signalling and excitation–contraction coupling contribute to muscle weakness. The plasma membrane network that carries the electrical excitation is moderately perturbed in the diseased muscle fibres. The excitation‐activated Ca 2+ input fluxes across both the plasma membrane and the membrane of the sarcoplasmic reticulum are defective in the diseased fibres, which probably contributes to muscle weakness in patients.